ANALISA KETIDAKSEIMBANGAN BEBAN TRANSFORMATOR DISTRIBUSI PADA GARDU 1A POLITEKNIK PENERBANGAN INDONESIA CURUG - HENDRO WIDIARTO; ASEP SAMANHUDI (KNOWLEDGE: Jurnal Inovasi Hasil Penelitian dan Pengembangan, 2022)
The distribution network is part of the electric power system in the form of a delivery network that connects the load center substation to the customer. The distribution network functions to distribute electrical energy to customers as needed. The distribution network in its operation cannot be separated from distribution substations and distribution transformers. Therefore, electrical substations and distribution transformers are an inseparable unit. Substation 1A is one of the electrical substations at the Curug Indonesian Aviation Polytechnic. To support the performance of the transformer so that it can work properly, it is necessary to pay attention to the condition of the transformer, as well as how large the percentage of the load imbalance is. A research will be conducted on the percentage of load imbalance on transformers A and B at Substation 1A of the Indonesian Aviation Polytechnic Curug. In this study, measurements of the value of the R, S, and T phase currents will be carried out in the transformer located at the 1A substation. After the measurement data will be processed, then the results of the data processing will be analyzed using descriptive analysis methods, which in the end will be presented that the percentage of load imbalance on the transformer at the 1A Indonesian Aviation Polytechnic Curug substation is on what criteria according to PLN rules (SK ED PLN No. 0017 .E/DIR/2014). From the results of measurements and data processing, data analysis was carried out with the results of the analysis that the percentage of transformer A load imbalance on the measurement on 5 July 2021 to 11 July 2021 was 25.17%, which was in the less criteria. Transformer B on the measurement on June 28, 2021 to July 4, 2021 is 25.73%, which is in the bad criteria. Transformer B on the measurement on 04 September 2021 to 10 July 2021 is 40.87%, is in the bad criteria. ABSTRAKJaringan distribusi merupakan bagian dari sistem tenaga listrik yang berupa jaringan penghantar yang menghubungkan antara gardu induk pusat beban ke pelanggan. Jaringan distribusi berfungsi mendistribusikan energi listrik ke pelanggan sesuai kebutuhan. Jaringan distribusi dalam operasinya tidak bisa dipisahkan dengan gardu induk distribusi dan transformator distribusi. Oleh karenanya gardu listrik dan transformator distribusi merupakan suatu kesatuan yang tidak dapat dipisahkan. Gardu 1A merupakan salah satu gardu listrik yang berada di Politeknik Penerbangan Indonesia Curug. Untuk menunjang kinerja transformator agar dapat bekerja dengan baik perlu diperhatikan kondisi transformatornya, serta perlu seberapa besar persentase ketidakseimbangan bebannya. Akan dilakukan penelitian mengenai seberapa besar persentase ketidakseimbangan beban pada transformator A dan B di gardu 1A Politeknik Penerbangan Indonesia Curug. Dalam penelitian akan dilakukan pengukuran nilai arus fasa R, S, dan T pada transformator yang berada pada gardu 1A. Setelah pengukuran data akan diolah, kemudian hasil olah data akan dianalisis dengan metode analisa deskriptif, yang pada akhirnya akan disajikan bahwa persentase ketidakseimbangan beban pada transformator di gardu 1A Politeknik Penerbangan Indonesia Curug berada pada kriteria apa sesuai dengan aturan PLN (SK ED PLN No. 0017.E/DIR/2014). Dari hasil pengukuran dan pengolahan data maka dilakukan analisis data dengan hasil analisis bahwa persentase ketidakseimbangan beban transformator A pada pengukuran tanggal 05 juli 2021 sampai dengan 11 juli 2021 sebesar 25.17 %, berada pada kriteria kurang. Transformator B pada pengukuran tanggal 28 juni 2021 sampai dengan 04 juli 2021 sebesar 25.73%, berada pada kriteria buruk. Transformator B pada pengukuran tanggal 04 september 2021 sampai dengan 10 juli 2021 sebesar 40.87 %, berada pada kriteria buruk.